Implications of the Globalizing Digital Retailing on Competition and Consumer Protection in COMESA Countries - Kabuganda, Steven Kamukama (Global journal of Business and Integral Security, 2023)
Digital retailing is among the major factors contributing to globalization of markets with a potential of boosting trade flows and transforming developing countries into global players. Despite this potential, developing countries are faced with digital retail competition and consumer protection related constraints which constrain competitiveness, efficient operations of the markets, full utilization of the technologies and optimizing consumer welfare. This situation is further exacerbated by the powerful global players whose practices with cross border effects cannot be easily addressed by countries due to jurisdictional limitations. This dissertation therefore sought to identify the challenges faced by the countries in the Common Market for Eastern and Southern Africa (COMESA), policy options and implementation approaches needed to address cross border effects of digital retail to promote effective competition and ensure consumer welfare while harnessing the potential of ecommerce. This research followed a comprehensive literature review, formulation of a conceptual framework and research questions, collection of data from experts in selected COMESA countries using questionnaires and face-to-face interviews and conducting systematic data analysis to generate conclusions and recommendations. The findings reveal that digital retail, aided by technology including complex algorithms and artificial intelligence, entails specific characteristics which enable platforms to gain economies of scale and scope, market power, winner-takes-all effects, network effects, lock-in effects and ability to operate in multiple or multisided markets which may enhance market concentration and encourage practices with adverse effects on the market ecosystem. Further, the study reveals that COMESA countries are faced with digital retail associated anticompetitive practices and conducts that lower consumer welfare particularly in merger control, detection of cartels, vertical restraints, abuse of market power along with other unilateral restraints and consumer protection concerns. Furthermore, the study establishes that existing laws of COMESA countries are limited in scope to effectively address digital retail specific concerns, especially conducts that increase concentration, reduce contestation, or diminish consumer welfare. This dissertation concludes that COMESA countries may need to enhance their institutional and legal framework, including the regional law to effectively regulate digital retail, address jurisdictional limitations and cross border effects on the Market.